TRENDS IN THE DEVELOPMENT OF INNOVATIVE ACTIVITY IN THE AGRO-INDUSTRIAL COMPLEX OF KAZAKHSTAN - G.Zh. Abdykerova; D.M. Aikupesheva; G.I. Jempeissova; G.A. Baytikenova (Academic Journal of Physical and Chemical Sciences, 2019)
Kazakhstan is the owner of reserves for the further growth of agricultural production and food, as a country with significant reserves of land suitable for farming, even taking into account adverse climatic conditions. In recent years, the situation in the agricultural production of the republic has been characterized by an increase in efficiency, the development of the food market, logistics, financial services in the village, and, as a result, several improvements in the quality of life in the village. Ensuring the innovation development of agriculture in Kazakhstan requires significant transformations of scientific and educational activities, the creation of a system for mastering the achievements of scientific and technological progress (technology transfer), optimization of the management structure and coordination of participants in the innovation process.